Design, synthesis, biological evaluation, NMR and DFT studies of structurally simplified trimethoxy benzamides as selective P‐glycoprotein inhibitors: the role of molecular flatness. (26th July 2016) - Stefanachi, Angela; Mangiatordi, Giuseppe Felice; Tardia, Piero; Alberga, Domenico; Leonetti, Francesco; Niso, Mauro; Colabufo, Nicola Antonio; Adamo, Carlo; Nicolotti, Orazio; Cellamare, Saverio
Abstract : In a recent investigation carried out on a panel of trimethoxybenzanilides, we showed that the formation of an intramolecular hydrogen bond is a key element for tuning P‐gp inhibitory activity. In this study, we designed new structurally simplified trimethoxy benzamides (5 –17, Table 1 ) with the aim to uncover the minimal molecular requirements needed for P‐gp inhibition. The new prepared smaller‐sized compounds exhibited IC50 in the low micromolar range. The combined use of NMR and DFT studies suggested that molecular flatness is causatively related to the P‐gp inhibition. Our results clearly pointed out that concerted theoretical and experimental approaches herein presented might be very helpful in addressing the design of structurally simplified and highly efficient compounds biasing P‐gp protein. Abstract : We designed new structurally simplified trimethoxy benzamides to detect the minimal molecular requirements for P‐gp modulation. The proposed ligands were provided with a high efficiency and IC50 values in the low micromolar range. By employing DFT and NMR approaches, we found a clear rationale bridging molecular flatness and P‐gp modulation.